Analysis of Correlation and Mapping of Chlorophyll-a Concentrations and Sea Surface Temperatures in Coastal Areas Based on Terra MODIS Satellite Image Data - Wibisana, Hendrata; Sukotjo, Bangun Muljo; Lasminto, Umboro (Makara Journal of Technology, 2021)
Ecosystems in aquatic environments are distinct from ecosystems on land. Changes that occur in ecosystems in aquatic environments affect the lives of biota in these waters, including the fish used as a food source in fishing communities in coastal areas. This study aims to determine the role of remote sensing in mapping and analyzing the relationship between the parameters of sea surface temperature and chlorophyll-a concentrations on the coast. The correlation of sea surface temperature with chlorophyll-a concentrations is modeled via linear regression. An analysis of variance test is performed to establish the suitability of the temperature data for the data on chlorophyll-a concentrations and to map the concentration distribution with the SeaDAS program. Results revealed a linear Chlor (mg/m3) = 63,695 − 2,014T (°C) with an R2 coefficient value of 0.325. This work concludes that Terra MODIS satellite imagery can be used to predict the distribution of chlorophyll-a concentrations on the coast, although its results require further comparison with those of other sensors.